2015
DOI: 10.3389/fncom.2015.00048
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic non-linear oscillator models of EEG: the Alzheimer's disease case

Abstract: In this article, the Electroencephalography (EEG) signal of the human brain is modeled as the output of stochastic non-linear coupled oscillator networks. It is shown that EEG signals recorded under different brain states in healthy as well as Alzheimer's disease (AD) patients may be understood as distinct, statistically significant realizations of the model. EEG signals recorded during resting eyes-open (EO) and eyes-closed (EC) resting conditions in a pilot study with AD patients and age-matched healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Dynamical models have also been fitted to neuroimaging data using a range of global optimisation methods. For example, mean field models have been fitted to EEG using particle swarm optimisation [ 52 ] and stochastic nonlinear oscillator models have been fitted to EEG using a multi-start algorithm [ 53 ]. Additionally, DCMs have been fitted to fMRI data using a method that combines local search with Gaussian process approximation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamical models have also been fitted to neuroimaging data using a range of global optimisation methods. For example, mean field models have been fitted to EEG using particle swarm optimisation [ 52 ] and stochastic nonlinear oscillator models have been fitted to EEG using a multi-start algorithm [ 53 ]. Additionally, DCMs have been fitted to fMRI data using a method that combines local search with Gaussian process approximation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have considered a stochastic limit cycle oscillator to model EEG signals [21][22][23] . They can also be modeled using networks of stochastic coupled nonlinear oscillators, with the dynamic unit described by the Duffing oscillator 24 or by Jansen's single-column model 25 . It was shown that a stochastic Duffing-van der Pol oscillator network model could capture the key characteristics of EEG signals, such as its time-varying power spectrum, Shannon entropy, and sample entropy of healthy controls and patients with a brain disorder.…”
Section: Related Workmentioning
confidence: 99%
“…More researchers are studying methods that can sensitively and conveniently monitor AD, involving cognitive neuropsychological detection, biochemical detection, neuroimaging detection, and so on. In recent years, electroencephalography (EEG) has become an important tool for studying human brain activity (Ghorbanian et al, 2015). Noninvasive EEG imaging methods are directly related to neural local field potentials and have a high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%